(untitled) (Journal of Open Law, Technology & Society, 2019)
Over the past several years, many companies have received warning letters in Germany for GPL non-compliance from a particular programmer – Patrick McHardy. In these letters, the programmer regularly claimed to own copyrights in parts of the Linux kernel and requested that the addressees sign cease-and-desist declarations – subject to the payment of contractual penalties to him personally, in the event of future instances of non-compliance. This article describes court proceedings in Germany opposing the programmer’s efforts, why Germany has been the venue of choice for these sorts of non-compliance assertions, how one particular company successfully defended itself, and discusses how other entities accused of non-compliance using these arguments can also pursue a successful defense.